Analisis Laju Korosi, Sifat Mekanik Baja Karbon Medium Terhadap Hasil Perlakuan Surface Treatment. - Destri; Septyani, Devi Eka (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
Metal-based equipment experiences several issues, one of which is corrosion. Corrosion on metals leads to significant losses. One way to inhibit the corrosion process is through metal coating. In this research, chromium is used as the coating material because it is heat-resistant and oxidation-resistant, preventing premature corrosion of the metal. The objective of this research is to study the characteristics of hard chromium plating combined with heat treatment on brake handle materials to inhibit corrosion, resulting in brake handles that are reliable and have good toughness. The research stages included the metal plating process with testing parameters of 0.9A and 1A current and testing time parameters of 30 minutes, 45 minutes, and 60 minutes. The tests conducted were hardness tests, weight loss tests, and microstructure tests using an optical microscope. Based on the research results, the longer the plating time, the greater the thickness and hardness of the coating. Likewise, the greater the current applied, the higher the coating thickness and hardness values.